Biogeographic Origin of Kurixalus (Anura, Rhacophoridae) on the East Asian Islands and Tempo of Diversification within Kurixalus - Qiumei Mo; Tao Sun; Hui Chen; Guohua Yu; Lina Du (Animals, 2023)
The ancestral area of Kurixalus on the East Asian islands is under dispute, and two hypotheses exist, namely that distribution occurred only on the Asian mainland (scenario of dispersal) and that wide distribution occurred on both the Asian mainland and the East Asian islands (scenario of vicariance). In this study, we conducted biogeographic analyses and estimated the lineage divergence times based on the most complete sampling of species, to achieve a more comprehensive understanding on the origin of Kurixalus on the East Asian islands. Our results revealed that the process of jump dispersal (founder-event speciation) is the crucial process, resulting in the distribution of Kurixalus on the East Asian islands, and supported the model of the Asian mainland origin: that Kurixalus on the East Asian islands originated from the Asian mainland through two long-distance colonization events (jump dispersal), via the model of vicariance of a widespread ancestor on both the Asian mainland and the East Asian islands. Our results indicated that choices of historical biogeography models can have large impacts on biogeographic inference, and the procedure of model selection is very important in biogeographic analysis. The diversification rate of Kurixaus has slightly decreased over time, although the constant-rate model cannot be rejected.